Use of Microsoft Access 2000 for timetable scheduling / Zin Ibrahim and Sharifah Akiman - Ibrahim, Zin; Akiman, Sharifah (2003)
Microsoft Access 2000, a database program, can assist the process of timetable scheduling. It uses a set of tables for lecturers, groups, subjects, rooms and slots as the reference for creating the timetable. There is a one-to-one relation by the elements of these groups using location, which is a combination of room and slot. Any additions or deletions to the time table will result in the change of these relationships. The system can also display the timetable according to lecturer, group or room.